Approaches to assessment in time-limited Mentalization-Based Therapy for Children (MBT-C) - Muller, Nicole; Midgley, Nick (Frontiers in Psychology, 2015)
In this article we describe our clinical approach to assessment, formulation and the identification of a therapeutic focus in the context of time-limited Mentalization-Based Treatment for Children (MBT-C) aged between 6 and 12. Rather than seeing the capacity to mentalize as a global construct, we set out an approach to assessing the developmental ‘building blocks’ of the capacity to mentalize the self and others, including the capacity for attention regulation, emotion regulation, and explicit mentalization. Assessing the child’s strengths and vulnerabilities in each of these domains provides a more nuanced picture of the child’s mentalizing capacities and difficulties, and can provide a useful approach to case formulation. The article sets out an approach to assessment that includes a consideration of mentalizing strengths and difficulties in both the child and the parents, and shows how this can be used to help develop a mutually agreed treatment focus. A clinical vignette illustrates the approach taken to assessment and connects it to routine clinical practice.